Decomposition of Chemical Nitrogen from Lightly Polluted Water with Volcanic Rocks Subsurface Wetland - Wang1, Hao; Li2, Xuejin (Asian Journal of Chemistry, 2013)
According to the problem of lightly polluted water in Wenyu river which secondary effluent was difficult to reach the water quality standard IV, some operation parameters of a new kind of constructed wetland technology were studied. The constructed wetland made water clean by the absorption of cobble layer, large and small particle volcanic rock layers, find sand layer, etc., the absorption of plants and the degradation of microorganisms. The results showed the optimal hydraulic retention time was 7 days. Meanwhile, after the treatment of constructed wetland, the effluent concentration of ammonia nitrogen and total nitrogen were from 0.2-1.1 mg/L and from 3.0-6.8 mg/L, respectively and the ammonia nitrogen and total nitrogen removal rates were from 54.2 to 91.7 % and from 29.2 to 68.8 %, respectively.